Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Review: 86

Answer

$(\sqrt 3,-3\sqrt 6)$

Work Step by Step

Let $P=(x_{1},y_{1})=(\sqrt 3,-2\sqrt 6)$ and $Q=(x_{2},y_{2})=(\sqrt 3,-4\sqrt 6)$ The midpoint formula is $(\frac{x_{1}+x_{2}}{2},\frac{y_{1}+y_{2}}{2})$. Substituting the values: Midpoint=$(\frac{x_{1}+x_{2}}{2},\frac{y_{1}+y_{2}}{2})$ Midpoint=$(\frac{\sqrt 3+\sqrt 3}{2},\frac{-2\sqrt 6-4\sqrt 6}{2})$ Midpoint=$(\frac{2\sqrt 3}{2},\frac{-6\sqrt 6}{2})$ Midpoint=$(\sqrt 3,-3\sqrt 6)$ Therefore, the coordinates of the midpoint are $(\sqrt 3,-3\sqrt 6)$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.